In vitro activities of three of the newer quinolones against anaerobic bacteria. - Wexler, H M (1992)
The antimicrobial activities of three new quinolone compounds, sparfloxacin, temafloxacin, and WIN 57273, against anaerobic bacteria were determined in three separate studies. The Wadsworth agar dilution technique using brucella-laked blood agar was used throughout. The activities of other antimicrobial agents, including ciprofloxacin, imipenem, chloramphenicol, metronidazole, cefotetan, cefoxitin, and amoxicillin-clavulanic acid, were also determined. The breakpoints of the new quinolones were 2 micrograms/ml for sparfloxacin and WIN 57273 and 4 micrograms/ml for temafloxacin. WIN 57273 displayed very good activity against anaerobes, inhibiting all strains of Bacteroides fragilis group species at 2 micrograms/ml. Only two strains of Fusobacterium species were resistant (MIC, 4 micrograms/ml). Sparfloxacin inhibited 78% of B. fragilis strains and 44% of other B. fragilis group isolates at 2 micrograms/ml. At 2 micrograms/ml, the percentages of other anaerobic species susceptible were as follows: B. gracilis, 70%; other Bacteroides species, 61%; Clostridium species, 50%; Fusobacterium species, 70%; Peptostreptococcus species, 91%; non-spore-forming gram-positive rods, 71%. Temafloxacin inhibited 91% of B. fragilis strains and 87% of other B. fragilis group species at 4 micrograms/ml. All strains of other Bacteroides species, 78% of Fusobacterium species, 80% of Clostridium species, and 90% of Peptostreptococcus species were inhibited at 4 micrograms of temafloxacin per ml.